Teaching Military English through collaborative tasks and war films - Rosca, Andrea; Oria Gómez, Beatriz (Didáctica. Lengua y Literatura, 2019)
Every successful language course should start with an identification of the students’ goals and an analysis of their present or future communicative needs to help them reach those goals. Regarding the teaching of the English language at the Centro Universitario de la Defensa, we have identified that the textbook proposes a general English and therefore, we have designed a personalized program that takes into account the cadets’ communicative needs and at the same time, allows them to familiarize themselves with military discourse. In this way, our educational proposal makes predominant use of Military English by combining collaborative tasks and war films. This study has two main objectives: on the one hand, to find out cadets’ perceptions and attitudes towards this innovative project and on the other hand, to check the impact of this methodology on cadets’ English level.